2010
DOI: 10.1007/s11104-010-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

Lonicera confusa has an anatomical mechanism to respond to calcium-rich environment

Abstract: Calcium (Ca) is an important nutrient element for plant growth and development. Nevertheless, excessive Ca restricts plant communities in Carich environments. Lonicera confusa DC. is one species adapted to Ca-rich environments in the karst area of southwest China; however, the anatomical mechanism that allows these plants to respond to a Ca-rich environment remains unclear. L. confusa was cultivated in two types of soil with controlled Ca levels. The ultrastructure of leaves at different developmental stages w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Therefore, it is likely that calcicole species have a tightly controlled or reduced uptake of Ca to survive in calcareous soils (Jefferies and Willis 1964, Raza et al 2000, Valentinuzzi et al 2015. In addition, they may have the capacity for compartmentation and/or physiological inactivation of Ca, such as producing Ca oxalate (Fink 1991, Webb 1999 or Ca sulfate (He et al 2014, Reid et al 2016, excreting Ca salts via stomata, or storing Ca 2+ in leaf glands and trichomes (Silva et al 1996, Charisios et al 2003, Wu et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that calcicole species have a tightly controlled or reduced uptake of Ca to survive in calcareous soils (Jefferies and Willis 1964, Raza et al 2000, Valentinuzzi et al 2015. In addition, they may have the capacity for compartmentation and/or physiological inactivation of Ca, such as producing Ca oxalate (Fink 1991, Webb 1999 or Ca sulfate (He et al 2014, Reid et al 2016, excreting Ca salts via stomata, or storing Ca 2+ in leaf glands and trichomes (Silva et al 1996, Charisios et al 2003, Wu et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for Lonicera confusa, which inhabits karst areas, excess Ca can not only be deposited within plants via storage in leaf glands and trichomes, but can also be excreted via stomata (Wu et al, 2010). In this study, significant positive selection signals were detected in the Primulina Ca 2þ -permeable channel TPC1, and a few sites were identified to be under positive selection.…”
Section: Discussionmentioning
confidence: 63%
“…We found that Ca-tolerant Lupinus species tended to have tight control over Ca uptake and/or translocation from roots to leaves, or better Ca compartmentation at the cellular level (Ding et al 2018a). These abilities likely play an important role in the tolerance of some Lupinus species to calcareous soils, as suggested for other calcicole species (He et al 2014;Jefferies and Willis 1964;Raza et al 2000;Valentinuzzi et al 2015;Webb 1999;Wu et al 2011).…”
Section: Introductionmentioning
confidence: 75%